TRADITIONAL FELTING OF THE KYRGYZ: TRADITIONS AND INNOVATIONS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article reveals the importance of felt handicrafts in the life of the Kyrgyz people in traditional society and the changes revealed in the modern period. Sheep wool is characterized as the main livestock raw material for the development of felting. Attention is paid to the technological stages of making felt carpets – ala kiyiz and shirdak, and some traditions and rituals accompanying the felt-making process are considered. Based on the conducted field ethnographic expeditions covering the territory of Naryn, Issyk-Kul and Chui regions, changes and innovations in the manufacture of felt carpets in the modern period have been revealed.
Keywords: wool, felt, tradition, changes, innovation, modernity, shyrdak.